The Hippo in the room: Targeting the Hippo signalling pathway for osteosarcoma therapies. Issue 3 (22nd July 2020) - Rothzerg, Emel; Ingley, Evan; Mullin, Benjamin; Xue, Wei; Wood, David; Xu, Jiake
Abstract: Osteosarcoma (OS) is a primary malignant bone tumour which usually occurs in children and adolescents. OS is primarily a result of chromosomal aberrations, a combination of acquired genetic changes and, hereditary, resulting in the dysregulation of cellular functions. The Hippo signalling pathway regulates cell and tissue growth by modulating cell proliferation, differentiation, and migration in developing organs. Mammalian STE20‐like 1/2 (MST1/2) protein kinases are activated by neurofibromatosis type 2, Ras association domain family member 2, kidney and brain protein, or other factors. Interactions between MST1/2 and salvador family WW domain‐containing protein 1 activate large tumour suppressor kinase 1/2 proteins, which in turn phosphorylate the downstream Yes‐associated protein 1/transcriptional coactivator with PDZ‐binding motif (YAP/TAZ). Moreover, dysregulation of this pathway can lead to aberrant cell growth, resulting in tumorigenesis. Interestingly, small molecules targeting the Hippo signalling pathways, through affecting YAP/TAZ cellular localisation and their interaction with members of the TEA/ATTS domain family of transcriptional enhancers are being developed and hold promise for the treatment of OS. This review discusses the existing knowledge about the involvement of the Hippo signalling cascade in OS and highlights several small molecule inhibitors as potential novel therapeutics. Abstract : The Hippo signalling pathway in osteosarcoma and highlights several small molecule inhibitors as potential novel therapeutics.